Cultural sensitivity in sexually transmitted infections (STIs) preventive campaign in Nigeria - Kadiri, Kehinde Kadijat (Elsevier Ltd., 2014)
The STIs preventive campaign in Nigeria lacks a common vision on how culture ought to inform the design and implementation of interventions.The study investigated how culture can be conceptualised into STIs preventive communication campaign in Nigeria. Data were gathered through in-depth interviews among students of Moshood Abiola Polytechnic, Abeokuta. Findings revealed virginity as one of the protective factors and polygamy as one of the risk factors in culture that must be taken into considerations.The study concludes that STIs preventive campaign in Nigeria needs to develop interventions that recognise not only the negative aspect of culture but also promote the positive and unique aspect of culture.